Aprendemos a contar utilizando recursos de mi entorno - Ruiz Zavaleta, Carmen Yane (2021)
The session entitled “We learn to count using resources from my environment” was developed in the area of Mathematics. Taking into account the competence of Solve quantity problems, the performance was achieved: he expresses with various representations and numerical language (numbers and verbal expressions) his understanding as cardinal when determining an amount of up to ten objects.Today, we live surrounded of various problem situations and it is necessary to use diverse materials that are available to students to solve of an appropriate way the problems that arise in the context starting from their own needs and interests. In the development of the session, motivational and challenging activities were applied that promoted the achievement of the competence and resolution capabilities. The didactic and pedagogical processes: motivation, activation of the previous knowledge, problematization, learning purpose, management, support and metacognition were also taken into account. The active participation of the students was promoted starting from previous knowledge that each student has and relating it to the new learning. The strategies used were according to their interests and needs that they showed.